Bagi Hasil Pertambangan Minyak Bumi Antara Pemerintah Pusat dan Pemerintah Daerah - Eko Nuriyatman (Program Studi Ilmu Hukum Universitas Maritim Raja Ali Haji, 2019)
Writing this scientific article is a research with normative (doctrinal) research method which aims to find out the legal review of the regulation of revenue sharing of petroleum mining between the central government and regional governments. This study uses an analysis of secondary data that the authors obtained from various literatures using the law approach, conceptual approach and case approach that occurs in everyday life regarding petroleum. The difference in the mechanism of distribution of funds and profit sharing between the central government and local governments results in imbalances in economic growth between all regions in Indonesia. The results of the research and analysis carried out by the authors indicate that the regulation of mintak mining revenue sharing funds between the central government and local governments through general allocation funds, special allocation funds and revenue sharing funds is in line with the objectives of regional autonomy, but lack of attention from the central the regions that have the highest natural resource income and lack of attention to development will lead to inequality between revenue sharing funds from the central government and regional governments. Supposedly with equal distribution between central government and regional government through policies in the form of natural resource priorities, it will create a main goal of the law, namely legal certainty, justice for some people and the last is to provide benefits to the community.